# A Visual Proof of the Derivatives of arcsin, arccos, and arctan Using a Cartesian Triangle

Mathematics –

Begin by imagining any point (x, y ) in R2 , we can create a right triangle with base x, height y , and hypotenuse x2 + y 2 ; let the angle at the origin θ:

6     r= x2 + y 2         θ  x -

y

We start by remembering our basic trigonometric identities: opposite hypotenuse adjacent cos θ = hypotenuse opposite tan θ = = adjacent sin θ = y r x = r y x =

1

To start with the derivative of arcsin, we must set r = 1, y = u, and so √ x = 1 − u2 .

6     1       θ  √ 1 − u2    u

Hence we ﬁnd the equation for sin θ has now become sin θ = y u = =u r 1

and so we have a deﬁnition of arcsin given by arcsin u = θ. The equation sin θ = u will be of more immediate use to us, so we now take the derivative of that equation with respect to u using the chain rule, d d sin θ = u du du dθ cos θ · =1 du dθ 1 = du cos θ However, it is worth noting that we can also develop a formula for cos θ 2

based on the image as well, cos θ = and so we can rewrite
dθ du

x = r

1 − u2 = 1

1 − u2 ,

as 1 dθ =√ . du 1 − u2

At this point, I draw your attention back to the fact that θ = arcsin u and so we have just shown that d 1 arcsin u = √ du 1 − u2 or with the diﬀerential rearranged, d(arcsin u) = √ du . 1 − u2

We can perform a similar operation for arccos which I will illustrate brieﬂy √ with r = 1, x = u, and y = 1 − u2 :

6     1      θ  u    √ 1 − u2

3

And so we have our cos θ given by cos θ = x u = = u. r 1

Taking the derivative of this equation with respect to u, we have d d cos θ = u du du dθ − sin θ · =1 du dθ −1 = du sin θ As in the previous section, we ﬁnd sin θ = we have d −1 arccos u = √ du 1 − u2 or if the diﬀerential is moved to the other side of the equation, d(arccos u) = − √ du . 1 − u2 √ 1 + u2 : √ 1 − u2 and since θ = arccos u,

For the arctan function we set x = 1, y = u, and r =

6    √  1+ u2       θ  1   u

4

By the design of this case, we have tan θ = and so arctan u = θ. As you might expect, we now take the derivative of the equation tan θ = u with respect to u, d d tan θ = u du du dθ sec2 u · =1 du dθ = cos2 u = 1 − sin2 u du As before, we ﬁnd our deﬁnition of cos θ, cos θ = 1 x =√ r 1 + u2 y u = = u, x 1

and so we substitute since θ = arctan u, d arctan u = du √ 1 1 + u2
2

=

1 , 1 + u2

or by shifting the diﬀerential to the other side of the equation, d(arctan u) = du . 1 + u2 du 1 − u2 d(arctan u) = du 1 + u2

d(arcsin u) = √

du 1 − u2

d(arccos u) = − √

5

Sign up to vote on this title